2017
DOI: 10.4236/ajcc.2017.64029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Elevated CO<sub>2</sub> on Wheat Growth and Yield under Free Air CO<sub>2</sub> Enrichment

Abstract: Impact of elevated CO 2 (free air CO 2 enrichment) was studied on wheat (Triticum aestivum L. var Kundan) growth, yield and proteome. Elevated CO 2 significantly impacted both underground (+24%) and aboveground (+15%) biomass. Grain weight/plant and harvest index were increased by 35% and 11.4%, respectively under high CO 2 . On the other hand, seed protein content was decreased by 19% under CO 2 enrichment while seed starch and soluble sugar contents were increased by 8% and 23%, respectively. Wheat leaf prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…The biomass production and water use efficiency of the plants exposed to elevated CO 2 condition too increased. The corresponding results were reported by (Barnes et al, 1995;Kannojiya et al, 2019;Lamichaney et al, 2021;Prakash et al, 2022;Pandey et al, 2017;Singh et al, 2018. Enhanced CO 2 level can lead to positive effects more in C 3 plants compared to C 4 plants (Mishra et al, 2013;Rawat and Melkania., 2015;Pleijel and Hogy, 2015).…”
Section: Grain Weight/spikesupporting
confidence: 78%
“…The biomass production and water use efficiency of the plants exposed to elevated CO 2 condition too increased. The corresponding results were reported by (Barnes et al, 1995;Kannojiya et al, 2019;Lamichaney et al, 2021;Prakash et al, 2022;Pandey et al, 2017;Singh et al, 2018. Enhanced CO 2 level can lead to positive effects more in C 3 plants compared to C 4 plants (Mishra et al, 2013;Rawat and Melkania., 2015;Pleijel and Hogy, 2015).…”
Section: Grain Weight/spikesupporting
confidence: 78%
“…Although this rate was still less than a rate measured through an experimental approach reported by Pandey et al . (), SBCMnSD outputs exhibited positive CO 2 coefficients across almost the entire region, instead of largely negative CO 2 coefficients with NonSBC outputs. Second, the coefficients associated with NonSBC yields varied dramatically, while those with SBCMnSD were much more consistent and closer to those previously reported.…”
Section: Resultsmentioning
confidence: 86%
“…It means that proteins and minerals are diluted by the increased photosynthetic assimilation of carbon, which poses a great threat to future food security because the calories in the food may be sufficient but undernourishment with essential mineral nutrients. For example, eCO 2 greatly increased the ratio of C to N by increasing the starch and total NSC concentrations and decreasing grain N concentration in wheat [63]. However, Taub et al [54] found that the magnitude of the negative eCO 2 effect on wheat grains was smaller under high soil N conditions than under low soil N with the decrease of grain protein concentrations by 9.8% and 16.4%, respectively, suggesting that the dilution effect may be compensated by a higher nutrient supply.…”
Section: The Effects Of Eco 2 On Wheat Plants and The Mechanisms Behindmentioning
confidence: 99%